Prenatal Sonographic Diagnosis of Klippel-Trenaunay-Weber Syndrome Associated with Umbilical Cord Hemangioma - Sahinoglu, Zeki; Uludogan, Mehmet; Delikara, Nuri M. (American Journal of Perinatology, 2003)
Klippel-Trenaunay-Weber syndrome (KTW), also known as angio-osteohypertrophy syndrome, is a complex developmental disorder characterized by asymmetric hemi-hypertrophy of limbs and trunk due to bony and soft tissue overgrowth that may extend across the midline, varicose veins, and cutaneous hemangiomata. This rare syndrome has been previously described in the prenatal period by ultrasonography, and in literature, there are quite different presentation of cases. We describe a case suggested as a KTW syndrome by prenatal ultrasonography. The sonographic appearance of an unilateral leg hypertrophy associated with irregular echolucent cystic areas was consistent with KTW syndrome. A spheric, weak-echogenic mass without any active blood flow located in the umbilical cord revealed by color Doppler ultrasonography was an unexpected finding. The postpartum examination confirmed the prenatal diagnosis.
Keywords: Klippel-Trenaunay-Weber (KTW) syndrome; prenatal diagnosis; hemangioma